1994
DOI: 10.1111/j.1468-0432.1994.tb00013.x
|View full text |Cite
|
Sign up to set email alerts
|

What Flexibility Do Women Offer? Comparing the Use of, and Attitudes to, Part‐Time Work in Britain and France in Retail Banking

Abstract: A much neglected aspect in the comparative literature on labour market flexibility has ignored how employers' use of flexibility is affected by national differences in labour market characteristics. In this paper the case of part‐time work, in the retail banking sector in Britain and France, is taken to show how the preferences of available female workers, together with differences in educational attainment, childcare provision, legal regulation, personnel policy and organizational culture affect employers' us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This view of the British labour market has received some support from comparative studies, although these usually emphasise the importance of the institutional context in which employers take their decisions. For instance, O'Reilly's (1994) case studies of the French and British banking industry showed how employers in the two countries provided rather different task structures and employment conditions for part‐timers in broadly comparable work settings. The French were more likely to emphasise functional flexibility and part‐timers were less likely to be used to meet short‐term fluctuations in work load.…”
Section: Interpretations Of the Skill Level Of Part‐time Work: The LImentioning
confidence: 99%
“…This view of the British labour market has received some support from comparative studies, although these usually emphasise the importance of the institutional context in which employers take their decisions. For instance, O'Reilly's (1994) case studies of the French and British banking industry showed how employers in the two countries provided rather different task structures and employment conditions for part‐timers in broadly comparable work settings. The French were more likely to emphasise functional flexibility and part‐timers were less likely to be used to meet short‐term fluctuations in work load.…”
Section: Interpretations Of the Skill Level Of Part‐time Work: The LImentioning
confidence: 99%
“…This allowed researchers to make connections between how state policies shaped labour supply through education and training as well as through the provision (or not) of childcare services. It allowed an understanding of how, and on what terms, women's labour supply was constituted in different societies (O'Reilly, 1994).…”
Section: Economic Production Social Reproduction and Youth Labour Market Segmentationmentioning
confidence: 99%
“…These emergent themes quickly led to a rich seam of comparative research into varieties of gendered employment and welfare systems. In the early volumes of GWO, Hunter and Rimmer () provided an overview of gender relations in the UK and Australia while three articles considered how comparative institutional factors were leading to differences across countries in employment practices and women's position within specific occupations, namely O’Reilly () in relation to banking, by Truss () in relation to secretarial work and by Hantrais and Walters () in relation to professional workers, namely lawyers and accountants, each comparing the UK and France, though Truss also included Germany. The outcome of this comparative work was to reveal both similarities and differences within gendered occupations, thereby further challenging the grand narratives of dual systems theory and providing also more specific analyses of the scope for different societal arrangements to generate difference in both the degree and manifest forms of gender equality.…”
Section: Gender Work and Organization: The State Of The Debate In 1994mentioning
confidence: 99%